Evolutionary dynamics of codon usages for peste des petits ruminants virus - Wang, Xin; Sun, Jing; Lu, Lei; Pu, Fei-yang; Zhang, De-rong; Xie, Fu-qiang (Frontiers in Veterinary Science, 2022)
Peste des petits ruminants virus (PPRV) is an important agent of contagious, acute and febrile viral diseases in small ruminants, while its evolutionary dynamics related to codon usage are still lacking. Herein, we adopted information entropy, the relative synonymous codon usage values and similarity indexes and codon adaptation index to analyze the viral genetic features for 45 available whole genomes of PPRV. Some universal, lineage-specific, and gene-specific genetic features presented by synonymous codon usages of the six genes of PPRV that encode N, P, M, F, H and L proteins reflected evolutionary plasticity and independence. The high adaptation of PPRV to hosts at codon usages reflected high viral gene expression, but some synonymous codons that are rare in the hosts were selected in high frequencies in the viral genes. Another obvious genetic feature was that the synonymous codons containing CpG dinucleotides had weak tendencies to be selected in viral genes. The synonymous codon usage patterns of PPRV isolated during 2007-2008 and 2013-2014 in China displayed independent evolutionary pathway, although the overall codon usage patterns of these PPRV strains matched the universal codon usage patterns of lineage IV. According to the interplay between nucleotide and synonymous codon usages of the six genes of PPRV, the evolutionary dynamics including mutation pressure and natural selection determined the viral survival and fitness to its host.